2014
DOI: 10.1002/yd.20084
|View full text |Cite
|
Sign up to set email alerts
|

Applying neurodevelopmental theory to school‐based drug misuse prevention during adolescence

Abstract: Adolescence is characterized by incredible development in the prefrontal cortex of the brain, which is responsible for behavioral and emotional self-regulation, and higher order cognitive decision-making skills (that is, executive function). Typically late prefrontal cortical development and its integration with limbic areas of the brain associated with reward, pleasure, novelty seeking, and emotion can contribute to substance misuse vulnerability during adolescence. In this chapter, literature on the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Another recent study suggested that musically trained children exhibit better verbal fluency and processing speed as well as increased activation of executive regions [47]. While cognitive training [48], neurofeedback training [49], and mindfulness training [50] are additional methods that have shown early positive results in improving executive deficits, the impact of these interventions on brain function has not yet been evaluated. Given the paucity of studies in this area, it is clear that more work is needed to understand how proposed educational interventions may impact EF at a neural level.…”
Section: Educational Interventionsmentioning
confidence: 99%
“…Another recent study suggested that musically trained children exhibit better verbal fluency and processing speed as well as increased activation of executive regions [47]. While cognitive training [48], neurofeedback training [49], and mindfulness training [50] are additional methods that have shown early positive results in improving executive deficits, the impact of these interventions on brain function has not yet been evaluated. Given the paucity of studies in this area, it is clear that more work is needed to understand how proposed educational interventions may impact EF at a neural level.…”
Section: Educational Interventionsmentioning
confidence: 99%
“…PATHS efficacy trials have demonstrated reductions in an array of behavioral outcomes with putative relationships to substance use, including externalizing (e.g., anger and conduct problems) and internalizing (e.g., anxiety and sadness) behaviors, peer aggression, and hyperactivity [32]. Confirming the underlying neuro-cognitive logic model, Riggs and colleagues demonstrated that, relative to control students, 2nd and 3rd grade children who participated in the PATHS curriculum demonstrated enhanced inhibitory control skills as measured by performance on the Stroop task at 9-month posttest, which mediated reduced rates of both externalizing and internalizing behaviors at 1-year follow-up [36,37]. …”
Section: Introductionmentioning
confidence: 99%
“…Impairment of the EFs may cause several challenges, like difficulties dealing with novel situations and forming a reasonable plan that considers the relevant details, the inhibition of inappropriate responses to situations, and increased distractibility [9]. A small group of studies has revealed that higher mindfulness is associated with better executive functioning [10].…”
Section: Introductionmentioning
confidence: 99%